The Influence of STEM-Based Learning on Students’ Critical Thinking Skills - Busnawir Busnawir; Ming Kiri; Chenda Dara (Yayasan Adra Karima Hubbi, 2025)
Background. The integration of Science, Technology, Engineering, and Mathematics (STEM) into education has gained significant attention for its potential to foster students’ critical thinking and problem-solving skills. Purpose. STEM-based learning emphasizes hands-on, inquiry-driven approaches that encourage students to engage in real-world applications of knowledge. However, the impact of STEM-based learning on students’ critical thinking skills remains a subject of debate. Method. This study investigates the influence of STEM-based learning on the development of critical thinking skills among high school students. The research employs a quasi-experimental design, with one group of students receiving STEM-based instruction and another following a traditional curriculum. Pre- and post-assessments of critical thinking skills were conducted using standardized critical thinking tests. Results. The findings reveal that students in the STEM-based learning group showed significant improvements in their critical thinking abilities, particularly in areas such as analysis, evaluation, and problem-solving. In contrast, the traditional curriculum group showed little to no improvement. Conclusion. The study concludes that STEM-based learning has a positive impact on enhancing students’ critical thinking skills, suggesting that incorporating STEM approaches into educational practices can better prepare students for complex real-world challenges.